2017
DOI: 10.1007/s00223-017-0292-1
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Compromises Both Cancellous and Cortical Bone Mass in Mice

Abstract: To clarify osteoporotic effects of ketogenic diet (KD) on cancellous and cortical bone compared with ovariectomy (OVX) in mice. Forty female C57BL/6J 8-week-old mice were randomly divided into SD+Sham, SD+OVX, KD+Sham, and KD+OVX groups, and fed for 12 weeks. The distal femur of trabecular bone and the middle femur of cortical bone were evaluated with Micro-CT scanning. The maximum bending force and stiffness of the tibia were calculated using a three-point bending test. Osteoblast and osteoclast expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
2
23
1
Order By: Relevance
“…KD led to cancellous and cortical bone loss in the tibia and humerus, which was consistent with findings of tibia bone loss in a previous study by our group (14). A previous study by our group demonstrated that KD specifically caused cortical bone loss of tibiae in mice when compared with ovariectomized mice (14). The present study also investigated the bone loss in middle of L4 vertebra and the humerus, providing a comprehensive overview of the bone loss under KD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…KD led to cancellous and cortical bone loss in the tibia and humerus, which was consistent with findings of tibia bone loss in a previous study by our group (14). A previous study by our group demonstrated that KD specifically caused cortical bone loss of tibiae in mice when compared with ovariectomized mice (14). The present study also investigated the bone loss in middle of L4 vertebra and the humerus, providing a comprehensive overview of the bone loss under KD.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical trials have suggested that KD is safe and efficient (11,12); however, it also resulted in a progressive loss of bone mineral content in pediatric patients, particularly in those with a low body mass index (BMI) (13). A previous study by our group confirmed that KD resulted in a significant bone loss in the tibia and reduced mechanical function in the femur of mice (14); such side effects in cancellous-rich bones, e.g. the vertebrae, are worthy of further investigation.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, it was firstly reported by Hahn that KD had deleterious effects on bone mass in children who maintained this regimen in long term (13). Our previous studies also confirmed that KD compromised bone micro-structures and reduced bone biomechanics in rodents (14)(15)(16)(17)(18). However, the different effects of streptozotocin-induced hyperglycemia and KD-induced hyperketonemia on bone microstructures and biomechanics have not been elucidated.…”
Section: Introductionsupporting
confidence: 63%
“…Results from a rodent study also supported our analysis to some degree. No significant alteration of osteocalcin on cellular levels was found in mice fed with ketogenic diet . Similarly, human data also suggested that no changes were found in osteocalcin levels in patients receiving ketogenic diet treatment .…”
Section: Discussionmentioning
confidence: 88%